An update of teriflunomide for treatment of multiple sclerosis - Oh J; O'Connor PW (Dove Medical Press, 2013)
Jiwon Oh,1,2 Paul W O’Connor2 1Department of Neurology, Johns Hopkins University, Baltimore, MD, USA; 2Division of Neurology, St Michael’s Hospital, Toronto, ON, Canada Abstract: There are a number of oral agents emerging as potential disease-modifying agents in multiple sclerosis (MS). Among these investigational agents, teriflunomide has shown promise in large, multicenter, phase III clinical trials with respect to safety and efficacy in relapsing MS patients, and is the latest disease-modifying agent approved for use in MS patients in the United States. This review will summarize teriflunomide's historical development, clinical pharmacology, studies in animals, clinical trials, and safety data, and will end with a discussion of the role of teriflunomide in MS in the context of existing treatment options. Keywords: teriflunomide, multiple sclerosis, clinical trials, review